Recreational football improves bone mineral density and bone turnover marker profile in elderly men. (5th June 2014) - Helge, E. W.; Andersen, T. R.; Schmidt, J. F.; Jørgensen, N. R.; Hornstrup, T.; Krustrup, P.; Bangsbo, J.
Abstract : This study examined the effect of recreational football and resistance training on bone mineral density (BMD) and bone turnover markers (BTMs) in elderly men. Twenty‐six healthy sedentary men (age 68.2 ± 3.2 years) were randomized into three groups: football (F; n  = 9) and resistance training (R; n  = 9), completing 45–60 min training two to three times weekly, and inactive controls (C; n  = 8). Before, after 4 months, and after 12 months, BMD in proximal femur (PF) and whole body (WB) were determined together with plasma osteocalcin (OC), procollagen type‐1 amino‐terminal propeptide (P1NP), and carboxy‐terminal type‐1 collagen crosslinks (CTX‐1). In F, BMD in PF increased up to 1.8% ( P  < 0.05) from 0 to 4 months and up to 5.4% ( P  < 0.001) from 0 to 12 months; WB‐BMD remained unchanged. After 4 and 12 months of football, OC was 45% and 46% higher ( P  < 0.001), and P1NP was 41% and 40% higher ( P  < 0.001) than at baseline, respectively. After 12 months, CTX‐1 showed a main effect of 43% ( P  < 0.05). In R and C, BMD and BTM remained unchanged. In conclusion, 4 months of recreational football for elderly men had an osteogenic effect, which was further developed after 12 months, whereas resistance training had no effect. The anabolic response may be due to increased bone turnover, especially improved bone formation.